(untitled) (Tikrit Journal of Veterinary Science, 2024)
This study used (40) laboratory mice whose average weight was (30 ± 3) grams, divided equally into four groups. The first group was injected subcutaneously with growth hormone at a concentration of 0.2 kilograms/mg between one day and another at a dose of 0.25 ml. for a period of three months. While the animals of second group were injected with 0.2mg/kg BW growth hormone and dosed orally with sage extract at a concentration of 50 mg/kg of body weight for three months. The third group was dosed with sage extract only, while the fourth group (control group) was not dosed or injected. The animals were dissected and samples were taken from the animals’ kidneys and prepared for histological study to study the tissue changes resulting from injection with growth hormone and dosing with sage extract. The results showed the absence of normal tissue pattern in the group of male mice injected with growth hormone, in contrast to the group of mice injected with growth hormone and dosed with sage extract, while no tissue changes appeared in the kidneys of mice dosed with sage extract